Pengaruh Knowledge Sharing Terhadap Kinerja Karyawan di Truntum Hotel Kota Padang - Putri, Deanita; Suyuthie, Hijriyantomi; Pratama, Vischa Mansyera (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
This research was conducted based on interviews conducted during pre-research at Truntum Hotel Padang, which found several problems related to Knowledge Sharing and Employee Performance such as lack of employee knowledge of the work station and not achieving the quantity of employee work. The purpose of this research is to analyze the effect of knowledge sharing on employee performance at Truntum Hotel Padang. The method in this research is quantitative, causal relationship. The population in this study were all employees at Truntum Hotel Padang, totaling 78 employees. The sampling technique used is non-probability sampling, which is a saturated sampling technique that uses the entire population as a sample. Sources of research data were obtained from primary data by distributing questionnaires to respondents, namely employees, then secondary data obtained from companies. The research instrument uses a questionnaire (questionnaire) with the arrangement based on a Likert scale. Instrument trials were carried out by means of validity tests and reliability tests. The results of this study (1) namely the knowledge sharing variable shows an adequate category with a percentage of 44%, (2) then on the Employee Performance variable it shows an adequate category with a percentage of 54%. (3) Based on the results of the hypothesis testing used, the regression coefficient equation is 0.397 with a sig value of 0.000 <0.05, meaning that every 1 point increase in Knowledge Sharing units increases 0.397 Employee Performance units. The R Square value is 0.150, meaning that the influence of the X and Y variables is 15%.